Silicone Breast Implants: A Rare Cause of Pleural Effusion - Shaik, Imam H. (Case Rep Pulmonol, 2015)
Pleural effusions are one of the rarest complications reported in patients with silicone gel filled breast implants. The silicone implants have potential to provoke chronic inflammation of pleura and subsequent pulmonary complications such as pleural effusion. Herein, we report a 44-year-old female who presented with left sided pleural effusion, six weeks after a silicone breast implantation surgery. The most common infectious, inflammatory, and malignant causes of pleural effusion were excluded with pleural fluid cytology and cultures. With recurrent effusion in the setting of recent surgery, the chemical reaction to silicone breast implants was sought and exploration was performed which revealed foreign body reaction (FBR) to silicone material. The symptoms dramatically improved after the explantation.